(untitled) (Research, Society and Development, 2024)
The National Curricular Matrix is a theoretical-methodological framework that guides the training actions of professionals in the area of public security. In the educational sphere, the instructor accreditation process at PMAL is regulated through notice nº 027/2015 published in BGO nº 230, of december, 16, 2015, based on bureaucratic criteria, such as length of experience and number of academic titles. With technological advances, registrations, previously carried out only in person, are made exclusively through the Electronic Information System. In view of this, the General Commander of PMAL, with the advent of the New Law on Tenders and Administrative Contracts, established a technical committee to devise proposals for the accreditation notice for instructors and monitors, establishing criteria and procedures for the selection, qualification and monitoring of these professionals. In this context, the central objective of this study was to integrate software into the PMAL Access Center, with emphasis on the aforementioned accreditation process. To this end, exploratory and descriptive research was used, as it provides the dissemination of information about a topic, outlining it and deepening knowledge, at the same time as observing and analyzing the occurrence of data. As a result, there was unanimity regarding the recognition of the benefits and improvements resulting from the insertion of the computerized system in PMAL Schools. Also, there was a high potential for optimizing bureaucratic criteria, as well as reducing the waiting time for teacher candidates, thus improving effectiveness and efficiency in this process.